Ketidaksetaraan Upah dan Diskriminasi Struktural: Politik Identitas dalam Pilihan Kerja Pemuda Indonesia - Ahmad Zidan Alghifari; Fiyoga Bayu Saputra; Dwi Wahyu Maulana Putra; Yusril Huda (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the reasons and experiences of Indonesian youth who choose to work abroad as a response to domestic employment conditions. Using a qualitative approach and case study method, four key informants who have worked abroad for two years were interviewed online. The results show that young people experience obstacles in obtaining decent work, such as a non-transparent recruitment system, the dominance of nepotism practices, low professional recognition, and limited space for development. The decision to work abroad is a form of resistance to an unfair social system, as well as an effort to build a better identity and future. These findings are analyzed using Ulrich Beck's risk society theory, which explains that individuals in the modern era face social risks due to the failure of the modernization system. This study recommends the need for reform of the employment system in Indonesia to be fairer, more inclusive, and pro-young generation.